Development of Genetic Diagnostic Methods for Detection for Novel Coronavirus 2019(nCoV-2019) in Japan - Shirato, Kazuya; Nao, Naganori; Katano, Harutaka; Takayama, Ikuyo; Saito, Shinji; Kato, Fumihiro; Katoh, Hiroshi; Sakata, Masafumi; Nakatsu, Yuichiro; Mori, Yoshio; Kageyama, Tsutomu; Matsuyama, Shutoku; et al. (Japanese Journal of Infectious Diseases, 2020)
During the emergence of novel coronavirus 2019 (nCoV) outbreak in Wuhan city, China at the end of 2019, there was movement of many airline travelers between Wuhan and Japan, suggesting that the Japanese population was at high risk of infection by the virus. Hence, we urgently developed diagnostic systems for detection of 2019 nCoV. Two nested RT-PCR and two real-time RT-PCR assays were adapted for use in Japan. As of February 8, 2020, these assays have successfully detected 25 positive cases of infection in Japan.